2018
DOI: 10.1002/biot.201800148
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Future Perspectives in 4D Bioprinting

Abstract: Three-dimensionally printed constructs are static and do not recapitulate the dynamic nature of tissues. Four-dimensional (4D) bioprinting has emerged to include conformational changes in printed structures in a predetermined fashion using stimuli-responsive biomaterials and/or cells. The ability to make such dynamic constructs would enable an individual to fabricate tissue structures that can undergo morphological changes. Furthermore, other fields (bioactuation, biorobotics, and biosensing) will benefit from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(116 citation statements)
references
References 122 publications
0
106
0
Order By: Relevance
“…The fabrication process should be balanced between the requirements for making robust biopolymer constructs and for achieving biologically relevant cell densities. In the future, the use of stimuli‐responsive hydrogels in bioprinting may contribute to the development of smart bioinks . Furthermore, despite being reported in different studies, multimaterial and multicellular bioprinting has been scarcely explored due to the complexity of the printer setup that generally does not allow precise cell compartmentalization .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication process should be balanced between the requirements for making robust biopolymer constructs and for achieving biologically relevant cell densities. In the future, the use of stimuli‐responsive hydrogels in bioprinting may contribute to the development of smart bioinks . Furthermore, despite being reported in different studies, multimaterial and multicellular bioprinting has been scarcely explored due to the complexity of the printer setup that generally does not allow precise cell compartmentalization .…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the use of stimuli-responsive hydrogels in bioprinting may contribute to the development of smart bioinks. [126] Furthermore, despite being reported in different studies, multimaterial and multicellular bioprinting has been scarcely explored due to the complexity of the printer setup that generally does not allow precise cell compartmentalization. [127] Natural tissues, such as skeletal muscle tissue, have complex multicellular anisotropic structure in relation with the nervous and vascular networks.…”
Section: Discussionmentioning
confidence: 99%
“…Four‐dimensional can be employed to produce 4D construct by adding cells to stimuli‐responsive hydrogels that can render constructs dynamic and responsive to changes, e.g., in temperature, pH, and electrical or magnetic fields . As this opens up new possibilities, it will also bring about new challenges.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…The concept of 4D emerged associated with biofabrication and, consequently, with bioprinting, and can be categorized into two main approaches, namely materials capable of deformation and structures that mature after printing Gao et al, 2016). Materials capable of deformation can also be called responsive materials that are able to reshape or change their function according to external stimuli such as water, temperature, pH, light, and electrical or magnetic fields (Momeni et al, 2017;Ashammakhi et al, 2018;Betsch et al, 2018;Miri et al, 2018;Armstrong and Stevens, 2019). There are several works exploring the stimuli-responsive materials in the biomedical field, such as Jamal et al (2013), who demonstrated that a bilayered PEG hydrogel construct selffolded, after immersed in aqueous medium, into cylindrical structures of different radii with no adverse effect on the encapsulated cells.…”
Section: In Situ Bioprintingmentioning
confidence: 99%